Wars and Betweenness : Big Powers and Middle Europe, 1918-1945 - Aleksov, Bojan; Piahanau, Aliaksandr (Central European University Press, 2020)
"The region between the Baltic and the Black Sea was marked by a set of crises and conflicts in the 1920s and 1930s, demonstrating the diplomatic, military, economic or cultural engagement of France, Germany, Russia, Britain, Italy and Japan in this highly volatile region, and critically damaging the fragile post-Versailles political arrangement. The editors, in naming this region as "Middle Europe" seek to revive the symbolic geography of the time and accentuate its position, situated between Big Powers and two World Wars. The ten case studies in this book combine traditional diplomatic history with a broader emphasis on the geopolitical aspects of Big-Power rivalry to understand the interwar period. The essays claim that the European Big Powers played a key role in regional affairs by keeping the local conflicts and national movements under control and by exploiting the region's natural resources and military dependencies, while at the same time strengthening their prestige through cultural penetration and the cultivation of client networks. The authors, however, want to avoid the simplistic view that the Big Powers fully dominated the lesser players on the European stage. The relationship was indeed hierarchical, but the essays also reveal how the "small states" manipulated Big-Power disagreements, highlighting the limits of the latters' leverage throughout the 1920s and the 1930s"--